BEBERAPA SEGI KEMUKJIZATAN ALQURAN (Hunafa: Jurnal Studia Islamika, 2008)
The iâjÃ¢z of the Qurâan, which scholars define as the idea that the Qurâan constitutes something exceeding the customary, associated with challenge (tahaddÃ®) and yet free from opposition, has received much attention from classical times to the modern era. Scholars have tried to determine what aspects of the Qurâan constitute iâjÃ¢z. Some of them have argued that language structure is an aspect of its iâjÃ¢z; some have pointed out that another aspect of iâjÃ¢z is the information provided about concealed events, including the stories about previous prophets and information about future events. Nevertheless, for the purpose of this article, the writer will discuss three aspects of iâjÃ¢z of the Qurâan only.Kata Kunci: iâjÃ¢z, kemukjizatan Alquran, mukjizat kebahasaan, mukjizat peristiwa masa lampau